A narrative review of refugee & asylum seekers’ transitions into & experiences of working in the United Kingdom National Health Service - Derek David Truong Farnham; Ross Goldstone (BMC Health Services Research, 2023)
Abstract Background The United Kingdom (UK) has a significant and rising population of refugees and asylum seekers, including many who have previously worked as healthcare professionals. Evidence shows they have struggled to join and successfully work in the UK National Health Service (NHS) despite initiatives designed to improve their inclusion. This paper presents a narrative review based on research surrounding this population to describe the barriers that have impeded their integration and possible ways to overcome them. Methods We conducted a literature review to obtain peer-reviewed primary research from key databases (PubMed, Web of Science, Medline, EMBASE). The collected sources were individually reviewed against predetermined questions to construct a cohesive narrative. Results 46 studies were retrieved, of which 13 satisfied the inclusion criteria. The vast majority of literature focussed on doctors with minimal research on other healthcare workers. Study review identified numerous barriers impeding the integration of refugee and asylum seeker healthcare professionals (RASHPs) into the workforce that are unique from other international medical graduates seeking employment in the UK. These include experiences of trauma, additional legal hurdles and restrictions on their right to work, significant gaps in work experience, and financial difficulties. Several work experience and/or training programs have been created to help RASHPs obtain substantive employment, the most successful of which have involved a multifaceted approach and an income for participants. Conclusions Continual work towards improving the integration of RASHPs into the UK NHS is mutually beneficial. Existing research is significantly limited in quantity, but it provides a direction for future programs and support systems.